CRIMINAL RESPONSIBILITY IN THE EXECUTION OF THE CONTRACT FOR THE PROCUREMENT OF THE GOVERNMENT - Murdian Murdian (Jurnal IUS Kajian Hukum dan Keadilan, 2016)
This research aims re to analyze of fault and responsibility in the performance of procurement. Legal issues that arise in this research are, how is the error form that conducted in government procurement performance, how is the criminal responsibilities in government procurement performance. This research is normative research which use statute, conceptual and historical approach. The legal research compiled by literature study. Based on research result, can be concluded that there is two form of fault in criminal law, are errors due to deliberate (dolus) and errors due to negligence.  Responsibilities form in government procurement performance are occupation, personal and corporation responsibilities, Keywords : Faults, Responsibilities and Criminal Law